2018
DOI: 10.1021/jacs.8b10769
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular Reductive C–N Cross Coupling of Nitroarenes and Boronic Acids by PIII/PV═O Catalysis

Abstract: A main group-catalyzed method for the synthesis of aryl- and heteroarylamines by intermolecular C–N coupling is reported. The method employs a small-ring organophosphorus-based catalyst (1,2,2,3,4,4-hexamethylphosphetane) and a terminal hydrosilane reductant (phenylsilane) to drive reductive intermolecular coupling of nitro(hetero)arenes with boronic acids. Applications to the construction of both Csp2–N (from arylboronic acids) and Csp3–N bonds (from alkylboronic acids) are demonstrated; the reaction is stere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
83
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(83 citation statements)
references
References 58 publications
0
83
0
Order By: Relevance
“…In this domain, reductive catalytic approaches employing formaldehyde, formic acid or carbon dioxide in combination with silanes or hydrogen gas have been reported . Alternative approaches include the photo‐reductive N ‐methylation of aniline over Au‐TiO 2 and the reductive C–N cross coupling of nitroarenes and boronic acids by P III /P V =O catalysis . Methanol can be employed as both the reductant and the C1 source for the reductive methylation of nitroarenes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this domain, reductive catalytic approaches employing formaldehyde, formic acid or carbon dioxide in combination with silanes or hydrogen gas have been reported . Alternative approaches include the photo‐reductive N ‐methylation of aniline over Au‐TiO 2 and the reductive C–N cross coupling of nitroarenes and boronic acids by P III /P V =O catalysis . Methanol can be employed as both the reductant and the C1 source for the reductive methylation of nitroarenes.…”
Section: Introductionmentioning
confidence: 99%
“…[8] Alternative approaches include the photo-reductive N-methylation of aniline over Au-TiO 2 [9] and the reductive C-N cross coupling of nitroarenes and boronic acids by P III /P V =O catalysis. [10] Methanol can be employed as both the reductant and the C1 source for the reductive methylation of nitroarenes. This attractive option, which avoids the use of expensive and/or hazardous reductants, has been developed using a variety of heterogeneous catalytic systems.…”
Section: Introductionmentioning
confidence: 99%
“…Diphenylamine (DPA) is primarily used as astabilizer for nitrocellulose explosives [1] and the detection of oxidizers, [2] whereas C-alkylated diphenylamines are widely used as antioxidants for the preservation of fruits, [3] oils, [4] and polymers. In addition, other methods, including P III /P V =Oc atalysis, [15] iodine, [16] sulfonium triflates, [17] various nanoparticle catalysts, [18] and Pd/C catalysis for the formationo fa rylamines from aliphatic substrates, [19] have also been reported. [7] Additionally,t riphenylamines are important for the preparation of optoelectronic materials.…”
mentioning
confidence: 99%
“…[10] Arylamines are commonly prepared from amine precursors through metal-catalyzedC ÀNc oupling reactions. In addition, other methods, including P III /P V =Oc atalysis, [15] iodine, [16] sulfonium triflates, [17] various nanoparticle catalysts, [18] and Pd/C catalysis for the formationo fa rylamines from aliphatic substrates, [19] have also been reported. In addition, other methods, including P III /P V =Oc atalysis, [15] iodine, [16] sulfonium triflates, [17] various nanoparticle catalysts, [18] and Pd/C catalysis for the formationo fa rylamines from aliphatic substrates, [19] have also been reported.…”
mentioning
confidence: 99%
“…[10,11] In this context, we have shown that af our-membered phospha-cycloalkane (i.e., the phosphetane 2,T able 1) in combination with ah ydrosilane terminal reductant provides an efficient organocatalytic platform for OATreactions.Such aphosphacatalytic system has been shown to promote efficient reductive OATf rom carbonyl [12] and nitro groups [13] by cycling in the P III /P V =Or edox couple to reveal carbon-and nitrogenbased reactive intermediates,r espectively.W ee nvisioned advancing this biphilic organophosphorus-catalyzed OAT concept to encompass deoxygenative processing of sulfonyl moieties to furnish reactive sulfur(II)-based electrophilic intermediates. [10,11] In this context, we have shown that af our-membered phospha-cycloalkane (i.e., the phosphetane 2,T able 1) in combination with ah ydrosilane terminal reductant provides an efficient organocatalytic platform for OATreactions.Such aphosphacatalytic system has been shown to promote efficient reductive OATf rom carbonyl [12] and nitro groups [13] by cycling in the P III /P V =Or edox couple to reveal carbon-and nitrogenbased reactive intermediates,r espectively.W ee nvisioned advancing this biphilic organophosphorus-catalyzed OAT concept to encompass deoxygenative processing of sulfonyl moieties to furnish reactive sulfur(II)-based electrophilic intermediates.…”
mentioning
confidence: 99%